2011
DOI: 10.1002/bjs.7594
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, nature and impact of error in surgery

Abstract: This study shows that errors are common in surgery, and that near misses are more frequent than errors with serious consequences. It is hypothesized that registration of near misses might prevent errors with serious consequences and thus improve quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 29 publications
(29 reference statements)
2
29
0
Order By: Relevance
“…Increasing public scrutiny of the quality of care provided by hospitals has prompted studies of the documentation, management, and prevention of complications [1-3]. In that context, safety and quality have become prominent criteria in the evaluation of surgical care.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing public scrutiny of the quality of care provided by hospitals has prompted studies of the documentation, management, and prevention of complications [1-3]. In that context, safety and quality have become prominent criteria in the evaluation of surgical care.…”
Section: Introductionmentioning
confidence: 99%
“…3 In surgery, there is a lack of a clear definition and grading system to classify negative outcome, which hampers the interpretation of results. 5 Considerable resources have been invested in measuring and reducing the rates of SAEs. The phrase surgical adverse events (SAEs) therefore better describes any deviation from the normal postoperative course that reflects safety in health care delivery.…”
mentioning
confidence: 99%
“…However, studies have shown that errors called near misses are common and that preventing them will, in the long run, reduce the incidence of error-related complications. 10,27,33 Our study is one of the few that has assessed the effect of error recording and/or reporting on the pattern of error in medical practice in general and the first in neurosurgery in particular. Many available error studies have reported only the incidence and pattern of medical errors and adverse events.…”
Section: Resultsmentioning
confidence: 99%